Sanders Pierce’s Semiotic Study: Aqua Life Pack 1100 ml - Wirawan, Junaidi (VCD: Journal of Visual Communication Design, 2022)
Almost all fast-moving consumer goods (FMCG) use plastic-based packaging because it is easy to shape, can be colored, and raw materials are easy and cheap. Aqua bottle packaging uses PET (Polyethylene Terephthalate) plastic, the problem occurs when the disposable packaging becomes waste, difficult to decompose, complex recycling process resulting in environmental pollution and even become one of the factors of climate crisis. Aqua presents Aqua Life products which are interesting to study semiotically what messages are contained in them. The method used in this research is qualitative, with a netnography approach, the instruments used are visual observations, news articles, and supporting data from various agencies and literature studies which are described and analyzed using Sanders Pierce’s semiotic theory. In this study, it can be concluded that…. the results of this research are expected to add insight in terms of visual design and appreciation of the campaign to recycle plastic waste into new forms of packaging in Indonesia. Keywords: plastic, packaging, recycling